Exploring the mechanism of Xiaoqinglong decoction in the treatment of infantile asthma based on network pharmacology and molecular docking. Issue 2 (13th January 2023) - Chen, Daman; Chen, Qiqi; Zhao, Kaibo; Guo, Yongqi; Huang, Yuxin; Yuan, Zehuan; Cai, Yujia; Li, Sitong; Xu, Jiarong; Lin, Xiaohong
Abstract : To explore the mechanism of Xiaoqinglong decoction (XQLD) in the treatment of infantile asthma (IA) based on network pharmacology and molecular docking. The active ingredients of fdrugs in XQLD were retrieved from Traditional Chinese Medicine Systems Pharmacology database and then the targets of drug ingredients were screened. The disease targets of IA were obtained from OMIM and Gencards databases, and the intersection targets of XQLD in the treatment of IA were obtained by Venny 2.1 mapping of ingredient targets and disease targets. Cytoscape software was used to construct active ingredient-intersection target network. The potential targets of XQLD in the treatment of IA were analyzed by protein-protein interaction network using STRING platform, and the Gene Ontology function and Kyoto Encyclopedia of Genes and Genomes enrichment analysis were obtained by R Studio software. AutoDock was used to perform molecular docking for verification. In this study, 150 active ingredients of XQLD were obtained, including quercetin, kaempferol, β-sitosterol, luteolin, stigmasterol, and so on. And 92 intersection targets of drugs and diseases were obtained, including interleukin 6 (IL6), cystatin 3, estrogen receptor 1, hypoxia inducible factor 1A, HSP90AA1, epidermal growth factor receptor and so on. There were 127 items of Gene Ontology enrichment analysis and 125 Kyoto Encyclopedia of Genes and Genomes enrichment results, showing that apoptosis, IL-17 signaling pathway, tumor necrosis factor signaling pathway, P13K-Akt signaling pathway and other pathways may play a key role in the treatment of IA by XQLD. The results of molecular docking showed that the key active ingredients including quercetin, kaempferol, β-sitosterol, luteolin, stigmasterol, and the core targets including IL6, cystatin 3, estrogen receptor 1, hypoxia inducible factor 1A, HSP90AA1, and epidermal growth factor receptor had good binding activity. Through network pharmacology and molecular docking, the potential targets and modern biological mechanisms of XQLD in the treatment of IA were preliminarily revealed in the study, which will provide reference for subsequent animal experiments and clinical trials.